Karakteristik Kimia dan Profil Asam Lemak Ikan Nila Merah (Oreochromis sp.) dari Umur Panen Berbeda - Laode Muhamad Hazairin Nadia; Wulandari Wulandari; Yunialdi Hapynes Teffu; Fatur Rahman Rustan; La Ode Abdul Fajar Hasidu (Universitas Sriwijaya, 2023)
Red tilapia is in demand by the public as a consumption fish because it has several advantages, namely thick flesh and high nutritional value. This study aims to determine the chemical characteristics and fatty acid profile of red tilapia with harvesting ages of 16, 20 and 24 weeks. This research method used a completely randomized design (CRD) and each carried out 3 replications. The analysis used is the actorial pattern with one factor (16, 20 and 24 week harvesting age treatment). Data were analyzed using Analysis of Variance (ANOVA) and Duncan Multiple Range Test (DMRT) at 95% confidence level. The results showed that the water and protein content increased with increasing harvesting age for red tilapia, while the ash and fat content decreased. The highest water and protein content at 24 weeks of harvest were 80.17% and 17.85%, respectively. Fatty acids in red tilapia consist of 4 SAFA, 1 MUFA and 3 PUFA. The highest fatty acid content of red tilapia, namely palmitic fatty acid, was 27.26% at harvest age of 24 weeks and increased with increasing harvest age.